2004
DOI: 10.1097/01.asn.0000139689.94776.7a
|View full text |Cite
|
Sign up to set email alerts
|

Selective Decrease in Urinary Aquaporin 2 and Increase in Prostaglandin E2 Excretion Is Associated with Postobstructive Polyuria in Human Congenital Hydronephrosis

Abstract: Abstract. This study was undertaken to determine the role of aquaporin 2 (AQP2) in the impaired urinary concentrating capacity observed in patients who underwent pyeloplasty because of congenital unilateral hydronephrosis as a result of pyeloureteral junction disease. Twelve children (mean age, 8 Ϯ 2 mo) were examined in the study. From day 1 to day 5 after surgery, the urine was collected separately from pyelostomy draining only from the postobstructed kidney and from the bladder catheter draining mostly from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 29 publications
3
32
1
Order By: Relevance
“…This is thought to be due to a variety of factors including decreased AQP expression, ischemic renal tubular damage and impaired ENaCs [94]. Increased PGE2 may play a role in the decreased AQP2 expression [95,96]. These defects, combined with decreased urinary concentrating capability, increased ANP, and the supernormal volume of fluid and solute, leads to dieresis [95].…”
Section: Nephrogenic Diabetes Insipidus (Ndi)mentioning
confidence: 99%
“…This is thought to be due to a variety of factors including decreased AQP expression, ischemic renal tubular damage and impaired ENaCs [94]. Increased PGE2 may play a role in the decreased AQP2 expression [95,96]. These defects, combined with decreased urinary concentrating capability, increased ANP, and the supernormal volume of fluid and solute, leads to dieresis [95].…”
Section: Nephrogenic Diabetes Insipidus (Ndi)mentioning
confidence: 99%
“…The vasopressin is an antidiuretic agent that acts on the receptors of basolateral membrane of kidney collecting duct cells, which causes the fusion of vesicles containing aquapurins into apical cells of the collecting ducts. As a consequence, an impermeable membrane converts into a waterpermeable membrane, through the action of aquapurins AQP2, AQP3, and AQP4 (8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, expression of aquaporin is downregulated after long lasting bilateral ureteral obstruction (BUO), suggesting a contribution to long-term polyuria and impairment of urinary concentrating capacity that happen after relief of OU (2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…One study examined 12 children who underwent pyeloplasty due to congenital unilateral hydro-nephrosis, as a result of pyeloureteral junction disease [11]. In this study, AQP 2 levels in post-obstructed kidneys were compared to non-obstructed kidneys for 5 days.…”
Section: Pathogenesismentioning
confidence: 99%
“…Moreover, in one study, while examining AQP 2, an increase in prostaglandins E-2 (PGE-2) was observed in the urine from the obstructed kidney. The authors hypothesized that increased PGE-2 (rho activation and subsequent formation of f-actin stress fibers) [12] may also be responsible for downregulation of AQP channels [11].…”
Section: Pathogenesismentioning
confidence: 99%